UPI National Education Museum as a Learning Resource and Space for Edutourism-Based Continuing Education (From Ordinary To Autonomous Unit) - Yulifar, Leli; Maftuh, Bunyamin; Purnomo, Budi S. (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2023)
Abstract When the Covid C-19 Pandemic hit the world, all museums in various parts of the world were closed, including the National Education Museum of Universitas Pendidikan Indonesia (UPI National Education Museum). This paper aims to explore how the UPI National Education Museum metamorphosed, and passed the pandemic period by continuing to provide services to the academic community, in its function as a learning resource and edutourism-based sustainable education space. Through a qualitative descriptive method with data collection techniques in the form of documentation studies and Focus Group Discussions (FGDs) with inductive analysis, it was found that the UPI National Education Museum in addition to carrying out its functions in the fields of education, research and recreation, also expanded it towards triple helix cooperation, involving the private sector / DUDI (Business and Industry World). To be able to carry out its mission, the UPI National Education Museum must change its status from an ordinary unit to an autonomous unit. This research recommendation by the university policy holders (UPI) is used as one of the academic texts in deciding the UPI National Museum to be the only unit in UPI that is autonomous with flexibility in presenting programs from outside, especially in collaboration with the private sector, known as triple helix. This means that the UPI National Museum has followed the trend of world museums, which carry out re-imagine and recovery movements when Covid C-19 begins to subside.